Practice of teacher training in learning English in the first grade, Santa Martha school, 2022 / Gema Massiel Gosden López, Gladys Auxiliadora Díaz Muñoz - Gosden López, Gema Massiel (2022)
This study about the practice of teacher training in the learning of the English language was carried out with the teacher and first grade students at the Santa Martha school, Guineo community of Siuna city, RACCN Nicaragua. Actually, the purpose was to analyze the practice of teacher training and the strategies implemented by the teacher to develop the English class. Actually, this research was developed under the qualitative paradigm, with an ethnomethodology approach and a descriptive level of depth. For the data collection, the techniques applied were: observation applied to teacher and students, as well as interview and focus group. With these techniques was possible to identify the strategies implemented by the teacher in the English class, and how they have affected the student´s learning process. It should be noted that within these strategies the use of games and music for learning and practicing English vocabulary. Therefore, it is important to mention that the practice of teacher training affect in a high manner with the students' behavior towards the class, it means, the enthusiasm with an effective learning, and better social interaction with their partner at the time to work in different tasks assigned by the teacher which contribute to have a better acceptation for the English Subject. In addition, a methodological strategy proposal is suggested to the teachers to expand the game chest, such as, Hopscotch, Shallop, roulette and What did you hear? also musical repertoire such as, the doll dressed in blue, baby shark, the days of the week, and the little chicks say pio, pio in order to allow the student to be the protagonist of their own learning and the teacher fulfills her role as motivator.